Insect meal as promising feedstuffs for sustainable poultry nutrition and production with emphasis on black soldier fly Hermetia illucens: an updated review - Attia, يوسف; Asiry , خالد; Alrefaei, ماجد; M. Almasoudi, نجيب; D. Al-qurashi, عادل; A.A. Mousaa, مجدي (Journal of King Abdulaziz University-Meteorology Environment and Arid Land Agriculture Sciences, 2022)
This paper aimed to review the recent advances in using insect meal in poultry nutrition to assess the suitable species, dietary inclusion level, and nutrients profile, advantage, and disadvantage as well. More than 50 research articles, review articles, short communications, and book chapters were obtained from various online databases i.e. Google Scholar, PubMed, and Scopus, using the following keywords insect breeding and insects in poultry nutrition, black soldier fly Hermetia illucens (BSF). The selected black soldier fly larvae (BSFL), and pupa (BSFP) are based on growing interest due to easy breeding, valuable protein resource, and economic value. The urgent needs for alternative and locally available feed resources have been substantially increased after the COVID-19 crisis due to different reasons such as lockdown, close of boards, airports, and seaports. Most developing countries are dependent on imported feedstuffs for animal nutrition which was greatly influenced during COVID-19, affecting animal feed chain supply for farm species. That has raised the need for alternative/nonconventional local protein sources to sustain animal protein production. The BSF is a promising and candidate feed resource based on recently published broilers, laying hens, Japanese quail, and ducks’ studies.